Improvement of the dielectric and ferroelectric properties in superlattice structure of Pb(Zr,Ti)O-3 thin films grown by a chemical solution route - Pontes, F. M.; Longo, Elson [UNESP]; Leite, E. R.; Varela, José Arana [UNESP] (American Institute of Physics (AIP), 2004)
Making heterolayered perovskite materials constitutes an approach for the creation of better dielectric and ferroelectric properties. In the experiment reported here, heterolayered PZT40/PZT60 films were grown on Pt/Ti/SiO2/Si (100) by a chemical solution deposition. The dielectric constant of the heterolayered thin film was significantly enhanced compared with that of pure PZT40 and PZT60 thin films. A dielectric constant of 701 at 100 kHz was observed for a stacking periodicity of six layers having a total thickness of 150 nm. The heterolayered film exhibited greater remanent polarization than PZT60 and PZT40 films. The values of remanent polarization were 7.9, 18.5, and 31 muC/cm(2), respectively, for pure PZT60, PZT40, and heterolayered thin films, suggesting that the superior dielectric and ferroelectric properties of the heterolayered thin film resulted from a cooperative interaction between the ferroelectric phases made from alternating tetragonal and rhombohedral phases of PZT, simulating the morphotropic phase boundary of this system. (C) 2004 American Institute of Physics.